2022
DOI: 10.1007/s43630-022-00336-7
|View full text |Cite
|
Sign up to set email alerts
|

Sonophotocatalytic degradation of malachite green in aqueous solution using six competitive metal oxides as a benchmark

Abstract: A comparison study examines six different metal oxides (CuO, ZnO, Fe3O4, Co3O4, NiO, and α-MnO2) for the degradation of malachite green dye using four distinct processes. These processes are as follows: sonocatalysis (US/metal oxide), sonocatalysis under ultra-violet irradiation (US/metal oxide/UV), sonocatalysis in the presence of hydrogen peroxide (US/metal oxide/H2O2), and a combination of all these processes (US/metal oxide/UV/H2O2). The effective operating parameters, such as the dosage of metal oxide nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The UV‐Vis diffuse reflectance spectra of the tested ZnO‐NPs has been studied previously in our laboratory and published by El‐Sawy et al (2023). They were investigated using the UV‐Vis diffuse reflectance spectroscopic technique.…”
Section: Methodsmentioning
confidence: 99%
“…The UV‐Vis diffuse reflectance spectra of the tested ZnO‐NPs has been studied previously in our laboratory and published by El‐Sawy et al (2023). They were investigated using the UV‐Vis diffuse reflectance spectroscopic technique.…”
Section: Methodsmentioning
confidence: 99%
“…196 A low electrical potential induced a reaction between Na x NiFe(CN) 6 and an alkaline solution, which resulted in the formation of partially oxidized Ni 3+ species via the elimination of hydrogen atoms from the hydroxyl groups. 197 The nickel ions underwent further oxidation to Ni 4+ states due to their sequential deprotonation at elevated potentials. Theoretical simulations indicated that the oxidation of oxygen ions is initiated by the Ni 4+ ions, which function as electrophilic centers and trigger anion redox processes to facilitate the OER.…”
Section: Application Of Pb and Pbamentioning
confidence: 99%
“…Various methods have been employed for the fabrication of these semiconductor sonophotocatalysts, some of the most common being; co-precipitation ( El-Sawy et al, 2022 ), hydrothermal ( Kumaresan et al, 2020 ), sol-gel ( Leroy et al, 2020 ; Norabadi et al, 2020 ) sonochemical ( Anandan and Ashokkumar, 2009 ) and the solvothermal ( Rashid et al, 2023 ) method. The focus of this review is to showcase the advances that have been made in the application of sonophotocatalysis in water and wastewater treatment, thus these synthesis methods are not detailed.…”
Section: Sonophotocatalysis Mechanismmentioning
confidence: 99%